2003
DOI: 10.3748/wjg.v9.i12.2786
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect ofangelica sinensispolysaccharide on experimental immunological colon injury in rats

Abstract: AIM:To study the effect of angelica sinensis polysaccharide (ASP) on immunological colon injury and its mechanisms in rats. METHODS:Immunological colitis model of rats was induced by intracolon enema with 2, 4, 6-trinitrobenzene sulfonic acid (TNBS) and ethanol. The experimental animals were randomly divided into normal control, model control, 5-aminosalicylic acid therapy groups and three doses of ASP therapy groups. The 6 groups were treated intracolonically with normal saline, normal saline, 5-aminosalicyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 37 publications
4
29
0
Order By: Relevance
“…They also found an increase of SOD levels in treatment groups compared to colitis model group. Liu et al (2003) obtained similar results according to SOD levels in TNBS plus ethanol induced experimental colitis as well. On the other hand, SOD levels decreased by the effect of AA were shown to be increased in our study following NAC treatment in accordance with the studies mentioned above.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…They also found an increase of SOD levels in treatment groups compared to colitis model group. Liu et al (2003) obtained similar results according to SOD levels in TNBS plus ethanol induced experimental colitis as well. On the other hand, SOD levels decreased by the effect of AA were shown to be increased in our study following NAC treatment in accordance with the studies mentioned above.…”
Section: Discussionsupporting
confidence: 70%
“…Toxic colitic injury has been shown to increase MDA levels in rats and on the contrary various agents used in the treatment of the disease were shown to decrease it (Paiva et al 2002;Liu et al 2003;Mahgoub et al 2003). In addition, NAC was also shown to decrease the levels of MDA in studies in which experimental damage was formed other than colitis (Aydin et al 2002;Ozaras et al 2003;Park et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, activity of CAT has been reported to be unchanged after acetic acid-induced colitis [44]. Regarding SOD, the existing reports support increased level of SOD in acetic acid model of colitis [44][45][46] and also in TNBS plus ethanolinduced colitis [47]. Decreased or increased activities of SOD and CAT both indicate an imbalance between oxidants and antioxidants within the tissue.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, genetic, immunological factors and oxidative stress factors are involved [2,3]. Several experimental IBD in vivo studies have showed increased antioxidant enzymes to metabolize the oxidative toxic intermediates [4,5]. Currently, there is no curative treatment and conventional pharmacological drugs had partial efficacy, being unable to maintain a long-term clinical remission [4,6,7].…”
Section: Introductionmentioning
confidence: 99%